Underutilized arid vegetables for income - Samadia, D K; Haldhar, S M; Verma, A K (Indian Horticulture, 2019)
Dryland horticulture has enormous scope in providing nutrition rich food, social security and eco-restoration to the inhabitants of desert and tribal areas. While assessing distinctness of hot arid and semi-arid agroclimate of Rajasthan, it is accomplished that non-availability of apposite crop–genotypes and production techniques are two prime limitations in success of vegetable culture. Traditionally, kachri (Cucumis melo var. callosus / agrestis), kakadia / snap melon (Cucumis melo var. momordica), mateera (Citrullus lanatus), tinda (Praecitrullus fistulosus) and guar (Cyamopsis tetragonoloba) are grown. Besides, khejri (Prosopis cineraria) is playing a vital role in long-established farming, and its tender pods are used for vegetable purpose. With the establishment of national centre in 1993 at Bikaner, systematic research was started for germplasm conservation and utilization in native crop-plants having vegetable potentialities. The crop-genotype studies over 45 vegetables at Central Institute of Arid Horticulture, demonstrated that there is a breathtaking scope in getting quality marketable yield adopting production site management concept (HBCPSMA), provided trait specific genotypes. With khejri models, higher yield in prioritized vegetable and income @ ``75,000–2,25,000 ha/year was obtained in comparison to the traditional cropping (``23,000–42,000). Thus, technological advancement in under-scored arid vegetables is a boon towards better income and nutrition in resource constrainted environment.